The Procession of the Holy Rosary at the Confraternity of the Rosario (1716) - Ferozan, Nilab (Confraternitas)

(untitled) (Iter Press, 2022)
This article examines the Holy Rosary procession of 1716 held by the Confraternity of the Most Holy Rosary at the Church of Santa Maria Sopra Minerva in Rome. Pope Clement XI and several cardinals attended this special procession to celebrate the Holy Roman Empire’s victory over the Ottomans. Careful examination of the available documents opens a window into understanding this procession’s material and liturgical components and the spiritual and social meaning embedded in the complex elements of celebrating the rites. Through processions such as these, the Rosario created a distinctive expression of Roman devotion and became a well-known contributor to the religious and festive life of Rome. This article thus argues that the Rosario processions served as spectacular political, social, and cultural pageants, as well as a hallowed ritual in which the confraternity showcased its devotions and its political and social affiliations, all the while functioning as a means for maintaining and reinforcing social status and civic identities.